Opening Open Universities: The Canadian Experience - Daniel, J. S.; Smith, W. A.S. (Canadian Journal of Higher Education, 1979)
This article examines, from an administrative/management perspective, the two open universities which have been created in Canada in the 1970’s, Athabasca University in Alberta and the Te´le´-universite´ in Que´bec. A study of the initial planning reveals that effective planning requires balanced attention to means and ends. The new management structures required for this type of institution, coupled with the climate of acute uncertainty in which it operates in the early days, require particularly able and committed leadership. That both institutions have been rather successful argues for the importance of the open university concept itself.